The Winning Percentage In Congkak Using A Randomised Strategy - Chuei Yee Chen; Fong Peng Lim; Kai Siong Yow; Shahrina Ismail (Research and Development Office, Prince of Songkla University, 2024)
Indexed by Scopus/ERA